Septal and Anterior Reverse Mismatch of Myocardial Perfusion and Metabolism in Patients With Coronary Artery Disease and Left Bundle Branch Block. Issue 20 (May 2015) - Wang, Jian-Guang; Fang, Wei; Yang, Min-Fu; Tian, Yue-Qin; Zhang, Xiao-Li; Shen, Rui; Sun, Xiao-Xin; Guo, Feng; Wang, Dao-Yu; He, Zuo-Xiang; Sinha., Partha
<x xml:space="preserve">Abstract</x> Abstract The effects of left bundle branch block (LBBB) on left ventricular myocardial metabolism have not been well investigated. This study evaluated these effects in patients with coronary artery disease (CAD). Sixty-five CAD patients with complete LBBB (mean age, 61.8 ± 9.7 years) and 65 without LBBB (mean age, 59.9 ± 8.4 years) underwent single photon emission computed tomography, positron emission tomography, and contrast coronary angiography. The relationship between myocardial perfusion and metabolism and reverse mismatch score, and that between QRS length and reverse mismatch score and wall motion score were evaluated. The incidence of left ventricular septum and anterior wall reverse mismatching between the two groups was significantly different (P < 0.001 and P = 0.002, respectively). The incidences of normal myocardial perfusion and metabolism in the left ventricular lateral and inferior walls were also significantly different between the two groups (P < 0.001 and P < 0.001, respectively). The incidence of septal reverse mismatching in patients with mild to moderate perfusion was significantly higher among those with LBBB than among those without LBBB (P < 0.001). In CAD patients with LBBB, septal reverse mismatching was significantly more common among those with mild to moderate perfusion than among those with severe perfusion defects (P = 0.002). The correlation between the septal reverse mismatch score and QRS length was significant (P = 0.026). In patients with CAD and LBBB, septal and anterior reverse mismatching of myocardial perfusion and metabolism was frequently present; the septal reverse mismatch score negatively correlated with the QRS interval.